2022
DOI: 10.24146/tk.1048628
|View full text |Cite
|
Sign up to set email alerts
|

Decay of Web References in Academic Publications: A Case of Turkish Librarianship Journal

Abstract: Amaç: Bu çalışmada Türk Kütüphaneciliği dergisindeki web alıntılarının erişim sorunlarının belirlenmesi amaçlanmaktadır. Yöntem: Bu amaçla Türk Kütüphaneciliği dergisinin 2005-2020 yılları arasındaki hakemli çalışmaların DergiPark arşivinden bibliyografik kayıtları indirilmiş ve seçilen yayın türlerine göre web alıntıları elde edilmiştir. Daha sonra web alıntılarının kullanım oranları, erişim seviyeleri, URL'lerin yarılanma ömürleri ve üst seviye alan adlarının erişilebilirliği analiz edilmiştir. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…In the Journal of the Society of Laparoscopic & Robotic Surgeons , Ott (2022) noted that in articles published in 2019 and 2020, 14.7% of citations were unavailable due to bad, broken or non‐existent links. Yayla (2022) found that 16%–59% of references in papers published in Turkish Librarianship between 2005 and 2020 were web‐based references ( n = 2619), displaying a 20.8% incidence of reference rot. Niveditha et al (2022) calculated, from a body of 102,718 web‐based citations in journals published between 2008 and 2017, 23.1% reference rot in 10 library and information science (LIS) journals and 15.7% reference rot in 10 communication and media studies journals.…”
Section: Examples Of Recorded Instances Of Reference Rot In the Acade...mentioning
confidence: 99%
“…In the Journal of the Society of Laparoscopic & Robotic Surgeons , Ott (2022) noted that in articles published in 2019 and 2020, 14.7% of citations were unavailable due to bad, broken or non‐existent links. Yayla (2022) found that 16%–59% of references in papers published in Turkish Librarianship between 2005 and 2020 were web‐based references ( n = 2619), displaying a 20.8% incidence of reference rot. Niveditha et al (2022) calculated, from a body of 102,718 web‐based citations in journals published between 2008 and 2017, 23.1% reference rot in 10 library and information science (LIS) journals and 15.7% reference rot in 10 communication and media studies journals.…”
Section: Examples Of Recorded Instances Of Reference Rot In the Acade...mentioning
confidence: 99%